The Role of State Regulation in Copyright Protection Within the Digital Ecosystem: A Case Study of TikTok - Tolinggilo, Havid Putra Awal; Nirwan Junus; Nurul Fazri Elfikri (Siyasah Dusturiyah: State Law Review, 2025)
This research examines copyright infringement on TikTok, addressing the paradox between creative freedom and intellectual property protection. Digital technology expansion enables artistic expression while simultaneously creating enforcement gaps due to low legal awareness and inadequate public literacy regarding Law No. 28 of 2014 on Copyright. The study analyzes how TikTok's policies including takedown mechanisms, safe harbor principles, and fair use doctrine function as legal instruments balancing innovation and legal certainty. Employing normative legal methodology, this research investigates the synergy between national regulations and platform policies in protecting creators' moral and economic rights. Analysis reveals the urgent need for contextual legal education and collaboration among government, platforms, and society to establish a just digital ecosystem respecting originality while cultivating ethical, globally competitive creative culture. Furthermore, the research emphasizes the state's role as a primary actor in establishing legal frameworks protecting copyright in digital spaces. Article 28C (1) of the 1945 Indonesian Constitution provides constitutional foundation that the state must provide effective regulatory mechanisms and law enforcement protecting citizens' works. Through administrative instruments including Ministerial Regulations on Information and Communications (Permenkominfo) and governmental agency authorities (DJKI, Kominfo) this study evaluates how public policy creates accountable and constitutionally compliant digital governance, ensuring equitable copyright protection in contemporary information ecosystems.